2017
DOI: 10.1371/journal.pone.0186839
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the population structure of Neisseria meningitidis in two Australian states: Victoria and Western Australia

Abstract: Neisseria meningitidis is the causative agent of invasive meningococcal disease (IMD). A recombinant vaccine called Bexsero® incorporates four subcapsular antigens (fHbp, NHBA, NadA and PorA) which are used to assign a Bexsero® antigen sequence type (BAST) to each meningococcal strain. The vaccine elicits an immune response against combinations of variants of these antigens which have been grouped into specific BAST profiles that have been shown to have different distributions within geographical locations thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
(40 reference statements)
1
10
0
Order By: Relevance
“…24 Meningococcal Antigen Typing System (MATS) has been reported to produce similar predicted vaccine coverage obtained using BAST profiling of serogroup B strains. 25 It has been suggested that induction of immunogenicity may be inferred by one of the four vaccine targets that may be sufficient to protect against invasive disease. 24 Our preliminary analysis based on limited number of N. meningitides serogroup B isolates (Israel, 2017) suggests an estimated strain coverage for 4CMenB ranging from 20% to 46.7%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…24 Meningococcal Antigen Typing System (MATS) has been reported to produce similar predicted vaccine coverage obtained using BAST profiling of serogroup B strains. 25 It has been suggested that induction of immunogenicity may be inferred by one of the four vaccine targets that may be sufficient to protect against invasive disease. 24 Our preliminary analysis based on limited number of N. meningitides serogroup B isolates (Israel, 2017) suggests an estimated strain coverage for 4CMenB ranging from 20% to 46.7%.…”
Section: Discussionmentioning
confidence: 99%
“…According to several BAST studies performed in various countries, the predicted strain coverage of 4CMenB vaccine according to the BAST antigens, varies between years and between countries. 24,25 A large study including 2016 confirmed IMD isolates from Great Britain and Ireland revealed variation of immunogenicity to at least one of 4 vaccine targets from 30.8% in 2010 to 22.8% in 2014. 24 A study from Australia showed a difference between 2 geographic regions, Victoria (VIC) and Western Australia (WA) in the years 2008-2012.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…71 In certain regions in Australia, annual coverages of 44-91% were predicted by BAST and MATS, from 20 0 0 to 2014. 70,72 In addition, the European meningococcal strain collection genome library (EMSC-GL) for the epidemiological year 2011-2012 was characterized with the BAST scheme. The EMSC-GL comprised 799 meningococcal strains causing IMD, submitted by 16 European countries, of which 65.7% were MenB.…”
Section: Bastmentioning
confidence: 99%